Molecular Mechanisms Underlying Anti-Inflammatory Actions of 6-(Methylsulfinyl)hexyl Isothiocyanate Derived from Wasabi (Wasabia japonica) - Takuhiro Uto; De-Xing Hou; Osamu Morinaga; Yukihiro Shoyama (Hindawi Limited, 2012)
6-(Methylsulfinyl)hexyl isothiocyanate (6-MSITC) is a major bioactive compound in wasabi (Wasabia japonica), which is a typical Japanese pungent spice. Recently, in vivo and in vitro studies demonstrated that 6-MSITC has several biological properties, including anti-inflammatory, antimicrobial, antiplatelet, and anticancer effects. We previously reported that 6-MSITC strongly suppresses cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), and cytokines, which are important factors that mediate inflammatory processes. Moreover, molecular analysis demonstrated that 6-MSITC blocks the expressions of these factors by suppressing multiple signal transduction pathways to attenuate the activation of transcriptional factors. Structure-activity relationships of 6-MSITC and its analogues containing an isothiocyanate group revealed that methylsulfinyl group and the length of alkyl chain of 6-MSITC might be related to high inhibitory potency. In this paper, we review the anti-inflammatory properties of 6-MSITC and discuss potential molecular mechanisms focusing on inflammatory responses by macrophages.